The Contribution of Density Functional Theory to the Atomistic Knowledge of Electrochromic Processes - Bruna Clara De Simone; Marta Erminia Alberto; Tiziana Marino; Nino Russo; Marirosa Toscano (Molecules, 2021)
In this review, we provide a brief overview of the contribution that computational studies can offer to the elucidation of the electronic mechanisms responsible for the electrochromism phenomenon, through the use of the density functional theory (DFT) and its time-dependent formulation (TDDFT). Although computational studies on electrochromic systems are not as numerous as those for other physico-chemical processes, we will show their reliability and ability to predict structures, excitation energies, and redox potentials. The results confirm that these methods not only help in the interpretation of experimental data but can also be used for the rational design of molecules with interesting electrochromic properties to be initiated for synthesis and experimental characterization.